2021
DOI: 10.1016/j.heliyon.2021.e07564
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio and platelet-lymphocyte ratio as novel risk markers for diabetic nephropathy in patients with type 2 diabetes

Abstract: Introduction: Diabetes mellitus causes serious complications such as diabetic nephropathy. Diabetic nephropathy is now the most common reason of chronic kidney disease. Inflammation plays a crucial role in development and progression of diabetic nephropathy. The aim of this study was to evaluate the relationship of Inflammatory markers (neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio) with diabetic nephropathy in Syrian patients. Materials and methods: A total of 158 patients with type 2 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 34 publications
6
30
3
1
Order By: Relevance
“…In concordance with our results, a study of Jaaban et al (22) which studied the relationship between NLR and level of albuminuria. They reported that there was highly significant difference between their studied groups as regard systolic and diastolic blood pressure and there was no significant difference between their studied groups as regard BMI.…”
Section: Discussionsupporting
confidence: 94%
“…In concordance with our results, a study of Jaaban et al (22) which studied the relationship between NLR and level of albuminuria. They reported that there was highly significant difference between their studied groups as regard systolic and diastolic blood pressure and there was no significant difference between their studied groups as regard BMI.…”
Section: Discussionsupporting
confidence: 94%
“…PLR, as a simple, rapid, inexpensive, stable, and reliable parameter, has been widely used to diagnose and/or predict the prognosis of various diseases. Jaaban et al [ 64 ] reported that a high PLR was significantly correlated with diabetic nephropathy and that PLR may serve as a predictor and prognostic risk marker of diabetic nephropathy. Liu et al [ 65 ] performed a meta-analysis and suggested that PLR was significantly elevated in retinal vein occlusion, with pooled mean differences of 21.49 (95% CI 10.03–32.95) and pooled area under the receiver operating characteristic curve of 0.621 (95% CI 0.452–0.741).…”
Section: Discussionmentioning
confidence: 99%
“…Mean absolute lymphocyte count among the patients with and without diabetic nephropathy was 2.2 x 10 3 /µL and 2.4 x 10 3 /µL respectively. They also observed significantly higher mean total leukocyte count, absolute neutrophil count, absolute lymphocyte count and platelet count was significantly higher among the patients with diabetic nephropathy in comparison to patients without diabetic nephropathy [11] .…”
Section: Discussionmentioning
confidence: 84%
“…In a previous study conducted by Khandare SA et al mean NLR among the patients with and without diabetic nephropathy was found to be 2.83 and 1.94 respectively (p-value < 0.05). Jaaban et al in their study also reported significantly higher NLR among patient with diabetic nephropathy (2.3) in comparison to the patients without diabetic nephropathy (1.73) (p-value < 0.05) [10,11] . .66 for the LMR, the sensitivity was 44%, the specificity: 92% (the ability of the LMR to predict DN risk); 2.2 for the NLR, the sensitivity: 84%, the specificity: 98%; 207 for the PLR, the sensitivity: 72%, and the specificity: 80%.…”
Section: Discussionmentioning
confidence: 99%